Different measurement approaches as sources of differences in data on the prevalence of peer violence - Velki, Tena (Array, 2014)
The goal of this research was to investigate the difference in results of prevalence of peer violence when using different measurement approaches (definitional and behavioral) and different data collecting methods (self-rating, peer rating, peer nomination, self-nomination). The article presents results from two different researches on two samples of school-aged children from two towns in Slavonia. Prevalence of peer violence, in both samples, was measured by self-rating method based on behavioral approach. Pupils from the first sample gave self-ratings and peer ratings of peer violence prevalence, based on definitional approach. Pupils from the second sample gave peer nomination and self-nomination of peer violence based on definitional approach. The results have shown a higher prevalence of peer violence when using definitional approach and the results were the same regardless of using peer ratings or self-ratings. Self-ratings methods based on behavioral approach and peer nomination based on definitional approach have shown same peer violence prevalence but a slightly higher prevalence was obtained when using self-nomination. The study shows that it is necessary to use multimethod approach when testing the peer violence prevalence.